Proceedings of the workshop ‘Biofortified food - Working together to get more nutritious food to the table in India’ - Mitra-Ganguli, Tora; Boyd, Katrina; Uchitelle-Pierce, Benjamin; Walton, Jenny (Elsevier, 2019)
HarvestPlus is the global leader in biofortification and has been leading biofortification efforts in India for nearly a decade. A workshop hosted by HarvestPlus was held in April 2019 in New Delhi to discuss ways to increase the scale, reach and impact of naturally nutritious (biofortified) foods in India by working in partnership with the food industry. This paper summarizes the output of that 2-day workshop. Harvest Plus is a not-for-profit organization that works with its partners to tackle hidden hunger and malnutrition. It leads the global effort to develop biofortified staple crops, explore their acceptability, efficacy and effectiveness, and scale up their availability to rural and urban populations who may not have access to diverse diet, fortified foods or supplements. Scaling the reach and impact of biofortified food through foods systems is a key strategy for HarvestPlus. In this regard, HarvestPlus has conducted research into the barriers for scale-up and co-created solutions to overcoming those barriers through partnership with the food industry. During this workshop, it emerged that there is significant demand from the food industry who see value in biofortification to both their business and the health of their customers and the country. Small working groups explored specific opportunities around supply chains, food products and composition, and consumers & markets. Several common themes emerged from the deliberations. All three groups identified lack of awareness as a major barrier to scale. More data on the health and nutrition impacts, as well as consumer and market research, is critically needed to build the food industry’s understanding of biofortified foods. Ensuring supply chain integrity, meeting manufacturing product standards, and developing strategic messaging for consumers were also mentioned repeatedly. Ending hidden hunger and managing a profitable food business can be done simultaneously and sustainably. By addressing the barriers to embedding biofortification into the food system, HarvestPlus aims to increase the access that families and communities have to nutritious seeds and foods.